Maternal and neonatal outcomes related to Zika virus in pregnant women in Southern Vietnam: An epidemiological and virological prospective analysis - Rebecca Grant; Thao Thi Thanh Nguyen; Manh Huy Dao; Hang Thi Thu Pham; Géraldine Piorkowski; Tai Doan Tan Pham; Thang Minh Cao; Loan Thi Kim Huynh; Quan Hoang Nguyen; Linh Dang Khanh Vien; Frédéric Lemoine; Anna Zhukova; et al. (Elsevier, 2021)
Background: In 2016-2017, 68 women in Southern Vietnam had RT-PCR confirmed Zika virus (ZIKV) infection during pregnancy. We report here the outcomes of the pregnancies and the virological analyses related to this outbreak. Methods: We collected clinical and epidemiological information from the women who were enrolled in the study. Medical records related to the pregnancy in 2016-2017 were retrieved for those who were not able to be enrolled in the study. Children born to women with ZIKV infection during pregnancy were also enrolled. Serum samples were evaluated for presence of ZIKV antibodies. Phylogenetic analyses were performed on Zika virus genomes sequenced from the 2016-2017 serum samples. Findings: Of the 68 pregnancies, 58 were livebirths and 10 were medically terminated. Four of the medical records from cases of fetal demise were able to be retrieved, of which one was consistent with congenital ZIKV infection. Of the 58 women with a livebirth, 21 participated in the follow-up investigation. All but two women had serologic evidence of ZIKV infection. Of the 21 children included in the study (mean age: 30.3 months), 3 had microcephaly at birth. No other clinical abnormalities were reported and no differences in neurodevelopment were observed compared to a control group. Phylogenetic analysis revealed a clade within the ZIKV Asian lineage and branch at the root of samples from the 2013-2014 French Polynesian outbreak. The prM S139N mutation was not observed. Interpretation: We have been able to demonstrate a clade within the ZIKV Asian lineage implicated in adverse pregnancy outcomes in Southern Vietnam. Funding: INCEPTION project (PIA/ANR-16-CONV-0005) and a grant received from BNP Paribas Simplidon.